The Quarry - Grossinger, Harvey (Book collections on Project MUSE., 1997)
At the heart of this collection of five short stories and the title novella is the powerful interconnection between parents and children, nostalgia and memory, and the collective emotional intimacies and transactions that configure human behavior. Incisive and witty meditations on the disruptions and difficulties of family life, the stories in The Quarry focus on the precariously balanced world of anxious and awkward sons and painfully failed or failing fathers. The title novella sifts through the irreparable moral and psychological confusion brought about by the Holocaust, following two famil.